Age-Related Vestibular Loss: Current Understanding and Future Research Directions - Allen,D; Ribeiro,L; Arshad,Q; Seemungal,BM (Frontiers in Neurology, 2017)
The vestibular system sub-serves a number of reflex and perceptual functions, comprisingthe peripheral apparatus, the vestibular nerve, the brainstem and cerebellarprocessing circuits, the thalamic relays, and the vestibular cerebral cortical network.This system provides signals of self-motion, important for gaze and postural control,and signals of traveled distance, for spatial orientation, especially in the dark. Currentevidence suggests that certain aspects of this multi-faceted system may deteriorate withage and sometimes with severe consequences, such as falls. Often the deterioration investibular functioning relates to how the signal is processed by brain circuits rather thanan impairment in the sensory transduction process. We review current data concerningage-related changes in the vestibular system, and how this may be important for cliniciansdealing with balance disorders.